Reconstruction Designs of Lost Ancient Chinese Machinery - Yan, Hong-Sen.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book presents an innovative approach for the reconstruction design of lost ancient Chinese machinery. By combining the creative mechanism design methodology with the mechanical evolution and variation theory, all feasible and appropriate designs that are consistent with the science theories and techniques of the subject's time period can be systematically recreated. South pointing chariots, walking machines (the wooden horse carriage and the wooden cow and gliding horse), the seismograph, and the astronomical mechanical clock, are used as illustrated examples. The cultural, scientific, and technological backgrounds of these achievements are explained. Before new literature and/or hardware evidences are found, this work provides a novel direction and a unique tool for studying the lost machinery in ancient China and around the world. Furthermore, after reacquaintance with invaluable ancient wisdom, we anticipate stimulating innovative machinery for our future.
Keywords: ENGINEERING; SCIENCE -- HISTORY; MECHANICAL ENGINEERING; ENGINEERING; MACHINERY AND MACHINE ELEMENTS; HISTORY OF SCIENCE; MECHANICAL ENGINEERING